Planning amid crisis and austerity: in, against and beyond the contemporary conjuncture. Issue 1 (2nd January 2020) - Tulumello, Simone; Saija, Laura; Inch, Andy
ABSTRACT: This article introduces the special issue 'Planning amid crisis and austerity: in, against and beyond the contemporary juncture'. It starts by acknowledging two limits of the existing body of literature on the planning/crisis/austerity nexus: on the one hand, the excessive reliance on cases at the 'core' of the financial crisis of 2007–2008, with impacts on the understanding of austerity as a response to economic crises; and, on the other, the limited attention given to the impacts of austerity on planning, and their implications for planning practice and research. Based on the contributions in the special issue, the article reflects on some lessons learned: first, the need for a more nuanced understanding of the multiple geographies and temporalities of crisis and austerity; second, the problematic standing of planning practice and research in the face of crisis and austerity; and, third, the potential and limitations of (local) responses and grassroots mobilizations in shaping alternatives.